Satisfaction study between different removable partial dentures - Vera Zambrano, Adalid Valentino (2025)
Partial edentulism is a common oral health problem that affects patients' quality of life by compromising functions such as mastication, phonation, and aesthetics. Removable partial dentures (RPDs) are an effective solution for rehabilitating these functions, with cobalt-chromium prostheses and flexible prostheses being the most prominent. The objective of this study was to conduct a literature review to determine the level of satisfaction of patients with RPDs, as well as to compare the advantages, limitations, and contraindications of both types of prostheses. Materials and methods: A systematic literature review was conducted using databases such as Scopus and Scielo. Search terms used included "removable partial denture," "patient satisfaction," "advantages," "limitations," and "contraindications." Studies published between 2006 and 2025, in English and Spanish, were included. These studies evaluated the satisfaction of adult patients with RPDs and compared at least two types of prostheses. Duplicate articles, single case studies, reviews lacking a clear methodology, and those that did not specify patient satisfaction assessment criteria were excluded. The results showed that flexible prostheses are valued for their aesthetics and initial comfort, but they have limitations in terms of long-term strength and stability. On the other hand, cobalt-chromium prostheses offer greater durability and structural support, although their aesthetics may be limited due to visible metal components. Conclusion: These findings highlight the importance of personalizing prosthesis selection according to patient needs, taking into account both aesthetics and function. Furthermore, they underscore the need for innovation in materials to improve the strength and durability of removable partial dentures.